2012
DOI: 10.1111/j.1600-6143.2011.03737.x
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Blockade Combines with CTLA4Ig and Sirolimus to Produce Mixed Chimerism in an MHC-Defined Rhesus Macaque Transplant Model

Abstract: In murine models, T-cell costimulation blockade of the CD28:B7 and CD154:CD40 pathways synergistically promotes immune tolerance after transplantation. While CD28 blockade has been successfully translated to the clinic, translation of blockade of the CD154:CD40 pathway has been less successful, in large part due to thromboembolic complications associated with anti-CD154 antibodies. Translation of CD40 blockade has also been slow, in part due to the fact that synergy between CD40 blockade and CD28 blockade had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 36 publications
6
61
1
Order By: Relevance
“…Multiple antibodies against CD40 have been tested, with efficacy on graft survival and effect on B-cell populations depending on the clone used: Chi220 (Pearson et al 2002;Adams et al 2005), 3A8 (Badell et al 2012a,b;Page et al 2012a), 4D11 (Imai et al 2007;Aoyagi et al 2009), ch5D12 (de Vos et al 2004), or 2C10 (Lowe et al 2012).…”
Section: Costimulation Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple antibodies against CD40 have been tested, with efficacy on graft survival and effect on B-cell populations depending on the clone used: Chi220 (Pearson et al 2002;Adams et al 2005), 3A8 (Badell et al 2012a,b;Page et al 2012a), 4D11 (Imai et al 2007;Aoyagi et al 2009), ch5D12 (de Vos et al 2004), or 2C10 (Lowe et al 2012).…”
Section: Costimulation Blockadementioning
confidence: 99%
“…Although the regimen was successful in inducing long-lasting mixed chimerism, the marrow was found to be rapidly rejected once the maintenance immunosuppression was stopped (Larsen et al 2010), and viral infections continued to be an issue (Kean et al 2007). Replacing CD154 blockade with CD40 blockade did not prolong marrow graft acceptance beyond the cessation of immunosuppression (Page et al 2012a). To date, the effect of these mixed chimerism regimens on solid organ transplantation has not been reported.…”
Section: Chimerismmentioning
confidence: 99%
“…However, translation of the anti-CD154 reagent into nonhuman primate and human studies has revealed an unexpected complication of thromboembolic events [10,11], which were because of platelet activation [12]. Thus, CD40 instead of its ligand has become an attractive target [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Crossing a one-haplotype mismatch barrier, worsened chimerism outcome further in contrast to two MHC-haplotype matched cohorts [47]. Donor kidney grafts were rejected in the one-haplotype mismatch setting despite ongoing immunosuppression with sirolimus, anti-CD40L, and CTLA4Ig [47,48], with costimulation-blockade resistant graft rejection being linked to the accumulation of CD95+ Tmem cells [49].…”
Section: Nonhuman Primate Studiesmentioning
confidence: 99%
“…Crossing a one-haplotype mismatch barrier, worsened chimerism outcome further in contrast to two MHC-haplotype matched cohorts [47]. Donor kidney grafts were rejected in the one-haplotype mismatch setting despite ongoing immunosuppression with sirolimus, anti-CD40L, and CTLA4Ig [47,48], with costimulation-blockade resistant graft rejection being linked to the accumulation of CD95+ Tmem cells [49].A group led by Tatsuo Kawai at Havard Medical School recently showed that the use of belatacept (but not abatacept) improved the success rates of transient chimerism and renal transplant acceptance [50]. These observations were made in a cynomolgus monkey BMT model employing an irradiation-based nonmyeloablative conditioning (including TBI, thymic irradiation, antithymocyte globulin for T-cell depletion and calcineurin inhibitors) [50].…”
mentioning
confidence: 99%